The geoenvironmental susceptibility of the Ribeirão Lajeado watershed – Tocantins - Ribeiro, Lucas Silva; Robaina, Luís Eduardo Souza; Cristo, Sandro Sidnei Vargas (Sociedade & Natureza, 2023)
The geoenvironmental study through the integration of natural elements with the use and land cover is a methodological proposal for strategic planning. In this sense, the objective of this article is to perform an analysis of geoenvironmental susceptibility from the use of multicriteria in the watershed of Ribeirão Lajeado. For this, the organization of cartographic materials was carried out, such as the drainage network, slope, lithology, soils, land use and cover and access routes, where normalized weights were established from the technique of the Hierarchical Analytical Process (AHP). This crossing generated the geoenvironmental susceptibility map, defined in four units, namely: I) low (flat top area with vegetation cover and no proximity to the access roads); II) medium (places with some human occupations or with wavy smooth relief); III) high (areas with wide occurrence of roads and abundant drainage network, susceptible to anthropic intervention, mainly related to agricultural activities and urban areas) and IV) very high (places with roads and portions of agricultural use with slopes greater than 15%, presence of fire scars and urban areas. Thus, the AHP technique presents itself as an important tool for geoenvironmental, especially in defining weights for the factors analyzed.